How AI Influences Buying Loyalty Of Urban Housewives - Windarsari, Wiwin Riski; Rostina (Journal Management & Economics Review (JUMPER), 2025)
This qualitative study examines the impact of AI-driven digital marketing on brand loyalty and purchase decisions among urban housewives in Jakarta, Indonesia. Against the backdrop of Indonesia’s rapid digital transformation marked by 73% internet penetration and a projected $104 billion e-commerce market, the research addresses critical gaps in understanding how AI tools (e.g., personalized recommendations, chatbots) intersect with cultural values, trust dynamics, and socioeconomic realities. Through phenomenological analysis of 30 in-depth interviews, findings reveal a core paradox: while 87% of participants valued AI’s convenience for streamlining household purchases, this utility coexisted with profound distrust toward data privacy and algorithmic transparency. Culturally, brand loyalty hinged on AI’s ability to embody local customs and hospitality, with polite, context-aware interactions driving 3x higher retention. Socioeconomic disparities further shaped engagement, as lower-income housewives actively limited AI exposure to avoid aspirational alienation. The study concludes by proposing a contextualized AI resonance framework prioritizing transparent intent, cultural humility, and human escalation to align technology with Jakarta’s communal ethos. These insights urge marketers to design culturally grounded AI systems that honor housewives’ dual roles as pragmatic consumers and cultural guardians.